1999
DOI: 10.1002/(sici)1097-4644(19990401)73:1<31::aid-jcb4>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro association of 14-3-3 epsilon isoform with calmodulin: Implication for signal transduction and cell proliferation

Abstract: Using a yeast two-hybrid screen, human 14-3-3 epsilon protein was found to interact with human calmodulin. In vitro binding assay between human 14-3-3 epsilon protein/peptide and calmodulin was demonstrated by native gel electrophoresis, and the interaction was shown to be calcium dependent. Our results, along with the association of the 14-3-3 epsilon protein with other signaling proteins, suggest that the 14-3-3 protein could provide a link between signal transduction and cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 29 publications
(25 reference statements)
1
22
0
3
Order By: Relevance
“…68,69 These proteins bind to a wide variety of regulatory proteins and thereby participate in signaling events leading to cell differentiation and proliferation. [70][71][72] The Src-related tyrosine kinases fyn and lyn were also activated upon SDF-1␣ stimulation, and fyn associated with SHP2. Fyn and lyn have been shown to associate with cbl and SHP2 and thereby regulate their functions.…”
Section: Discussionmentioning
confidence: 99%
“…68,69 These proteins bind to a wide variety of regulatory proteins and thereby participate in signaling events leading to cell differentiation and proliferation. [70][71][72] The Src-related tyrosine kinases fyn and lyn were also activated upon SDF-1␣ stimulation, and fyn associated with SHP2. Fyn and lyn have been shown to associate with cbl and SHP2 and thereby regulate their functions.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 19 specific binding proteins we identified, 13 were those proteins previously been found to associate with 14-3-3 family proteins by other methods [13,18,19,24,25], while the other 6 proteins including SKb1Hs, p54 nrb , serine/threonine kinase 38, MEP50, 14-3-3 and cofilin 2 were newly identified 14-3-3 interacting partners in our study. Among the 13 known binding proteins (M2-PK, GAPDH, peroxiredoxin 6, thioredoxin, HSP90, HSP70, Bip, calmodulin, actin, 14-3-3, cofilin1, kinesin-related protein and tropomyosin 3), only four proteins including calmodulin, 14-3-3, cofilin1 and kinesin-related protein were known to associate with the isoform bait 14-3-3, while the other nine proteins were those previously identified by interacting with other 14-3-3 proteins [6,9].…”
Section: Quantitative Identification Of 14-3-3 Interacting Proteins Umentioning
confidence: 54%
“…Therefore, assisted by the 'in-spectra' quantitative markers of amino acid tags, we set more stringent threshold to distinguish the specific interactions in high precision which probably led to lose several weak interacting partners of 14-3-3 in compared to what were reported previously to bind with other isoform. We found that some of 23 non-specific proteins classified in our case were identified as the 14-3-3-binding partners in other studies [13,18,19,24,25]. For example, the proteins including HSP60, actin binding protein (filamin), alpha actinin, spectrin beta, H + -ATP synthase alpha subunit, H + -ATP synthase beta subunit, ribosomal protein P0 and ribosomal protein P2, which were excluded from Fig.…”
Section: Quantitative Identification Of 14-3-3 Interacting Proteins Umentioning
confidence: 55%
See 1 more Smart Citation
“…Therefore, the possibility could not be excluded that some 14-3-3 binding partners were not detected due to imperfect phosphorylation of the proteins on the array or due to 14-3-3 isoform-specific binding. Calmodulin, another known 14-3-3 interactor (Luk et al, 1999), was included as a negative control on the array and identified as negative in the present study, because the calciumdependent interaction between 14-3-3 and calmodulin could not be detected under the calcium-free conditions we employed. The known 14-3-3-binding proteins, which were spotted on the protein microarray but were not detected in the present study are listed.…”
Section: Discussionmentioning
confidence: 99%